Mapping water availability, cost and projected consumptive use in the eastern United States with comparisons to the west. (18th January 2018) - Tidwell, Vincent C; Moreland, Barbie D; Shaneyfelt, Calvin R; Kobos, Peter
Abstract: The availability of freshwater supplies to meet future demand is a growing concern. Water availability metrics are needed to inform future water development decisions. With the help of water managers, water availability was mapped for over 1300 watersheds throughout the 31 contiguous states in the eastern US complimenting a prior study of the west. The compiled set of water availability data is unique in that it considers multiple sources of water (fresh surface and groundwater, wastewater and brackish groundwater); accommodates institutional controls placed on water use; is accompanied by cost estimates to access, treat and convey each unique source of water; and is compared to projected future growth in consumptive water use to 2030. Although few administrative limits have been set on water availability in the east, water managers have identified 315 fresh surface water and 398 fresh groundwater basins (with 151 overlapping basins) as areas of concern (AOCs) where water supply challenges exist due to drought related concerns, environmental flows, groundwater overdraft, or salt water intrusion. This highlights a difference in management where AOCs are identified in the east which simply require additional permitting, while in the west strict administrative limits are established. Although the east is generally considered 'water rich' roughly a quarter of the basins were identified as AOCs; however, this is still in strong contrast to the west where 78% of the surface water basins are operating at or near their administrative limit. Little effort was noted on the part of eastern or western water managers to quantify non-fresh water resources.